Matrix Metalloproteases in Arterial Hypertension and their Trend after Antihypertensive Treatment - Eugenia Hopps; Rosalia Lo Presti; Gregorio Caimi (Karger Publishers, 2017)
Background/Aims: Arterial hypertension is characterized by vascular remodelling, atherosclerosis and cardiovascular complications. Matrix metalloproteases (MPPs) are endopeptidases produced by all the cells present in the vascular wall and are involved in the regulation of the extracellular matrix protein turnover. MMPs contribute to blood vessel formation, remodelling, angiogenesis; whereas an altered expression or activity of MMPs or their tissue inhibitors (TIMPs) results correlated with the development and progression of cardiovascular complications. Methods: We examined the literature data regarding the role of MMPs in human hypertension, including their involvement in vascular remodelling, and the effects of some antihypertensive molecules on these MMP/TIMP profile. Results: The expression and the activity of some MMPs and TIMPs are impaired in human hypertension. An altered MMPs/TIMPs balance plays an important role in the vascular wall rearrangement, in response to hemodynamic changes which may induce myocardial hypertrophy and fibrosis leading to ventricular remodelling. Several studies have examined the effects of some antihypertensive molecules, such as ACE inhibitors, angiotensin receptor blockers, calcium-channel blockers, and aldosterone antagonists, on the MMPs/TIMPs profile by obtaining positive results. Conclusion: Considering the data taken into consideration, the authors believe that in clinical practice a strategic antihypertensive therapy directed to the MMPs profile, may be useful to decrease the risk of cardiovascular complications.